Suppliers, Investors, and Equity Market Liberalizations - Martin Strieborny (Lund University, School of Economics and Management, Department of Economics, 2013)
Equity market liberalizations allow foreign investors to acquire ownership stakes in domestic firms. Previous research on the real impact of these events has therefore emphasized the interactions between firms and investors. This paper shows that cross-border equity flows also improve buyers-suppliers relationships with positive ramifications for economic growth. Firstly, a buyer backed by foreign capital means a smaller probability of contract failure due to default or some liquidity problems. Secondly, liberalization-driven improvements in public and corporate governance decrease the risk of a deliberate breach of contract. Cross-border equity flows can thus reassure upstream firms about the financial stability and contractual reliability of their corporate customers. Results from panel data and event-study approach confirm that equity market liberalizations boost output growth particularly in industries dependent on the trust of their suppliers, establishing a novel channel from financial globalization to the real economy.
Keywords: F36; F43; G15; G30; 330; cross-border equity flows; equity market liberalizations; finance and product markets; foreign ownership; …financial globalization and growth